Believing in Accordance with the Evidence New Essays on Evidentialism - McCain, Kevin; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This volume explores evidentialism, a major theory of epistemic justification. It contains more than 20 papers that examine its nuances, its challenges, as well as its future directions. Written by leading and up-and-coming epistemologists, the papers cover a wide array of topics related to evidentialism. The contributors present both sides of the theory: some are advocates of evidentialism, while others are critics. This provides readers with a comprehensive, and cutting-edge, understanding of this epistemic theory. Overall, the book is organized into six parts: The Nature of Evidence, Understanding Evidentialism, Problems for Evidentialism, Evidentialism and Social Epistemology, New Directions for Evidentialism, and Explanationist Evidentialism. Readers will find insightful discussion on such issues as the ontology of evidence, phenomenal dogmatism, how experiences yield evidence, the new evil demon problem, probability, the Path Principle, norms of credibility, intellectual virtues, wisdom, epistemic justification, and more. This title provides authoritative coverage of evidentialism, from the latest developments to the most recent philosophical criticisms. It will appeal to researchers and graduate students searching for more information on this prominent epistemological theory.
Chapter 1. Evidentialism: A Primer (Kevin McCain) -- Part I: The Nature of Evidence. Chapter 2. From Experience to Evidence: Sensory and Testimonial (Todd R. Long) -- Chapter 3. The Evidence in Evidentialism (Matthew McGrath) -- Chapter 4. Seemings, Reasons, and Knowledge: A Defense of Phenomenal Conservatism (Trent Dougherty) -- Chapter 5. Phenomenal Dogmatism, Seeming Evidentialism and Inferential Justification (Berit Brogaard) -- Part II: Understanding Evidentialism. Chapter 6. Between Belief and Disbelief (Earl Conee) -- Chapter 7. Metacognition as Evidence for Evidentialism (Matthew Frise) -- Chapter 8. Externalist Versions of Evidentialism (Michael Bergmann) -- Part III: Evidentialism and Social Epistemology. Chapter 9. An Evidentialist Social Epistemology (William D. Rowley) -- Chapter 10. Credibility and the Distribution of Epistemic Goods (Jennifer Lackey) -- Chapter 11. Evidentialism and Moral Encroachment (Georgi Gardiner) -- Part IV: Challenges for Evidentialism -- Chapter 12. A Probabilistic Critique of Evidentialism (Michael Huemer) -- Chapter 13. Standing in a Garden of Forking Paths (Clayton Littlejohn) -- Chapter 14. Evidentialism, Time-Slice Mentalism, and Dreamless Sleep (Andrew Moon) -- Chapter 15. No Kind of Reason is the Wrong Kind of Reason (Miriam Schleifer McCormick) -- Part V: New Directions for Evidentialism -- Chapter 16. Evidentialism, Hope, and Wisdom: Are Evidentialist Theories of Wisdom Hopeless? (Sharon Ryan) -- Chapter 17. A Central Role for Epistemic Virtues in Evidentialism (Sarah Wright) -- Chapter 18. Whither Evidentialist Reliabilism? (Juan Comesaña) -- Part VI: Explanationist Evidentialism -- Chapter 19. Evidentialism and Explanatory Fit (Richard Fumerton) -- Chapter 20. Propositionalism and McCain s Evidentialism (Jonathan L. Kvanvig) -- Chapter 21. Is Evidential Fit Grounded in Explanatory Relations? (Matthias Steup) -- Chapter 22. Explanationist Evidentialism: A Defense (Kevin McCain).
Keywords: Epistemology; Social sciences; Philosophy and social sciences; Epistemology; Methodology of the Social Sciences; Philosophy of the Social Sciences